The Role of Artificial Intelligence on Enhancing Customer Experience - Abu Daqar, Mohannad A.M.; Smoudy, Ahmad K. A. (International Review of Management and Marketing, 2019)
The main aim of the study is to examine the role of Artificial Intelligence (AI) on Enhancing Customer Experience in Palestine through different industries, such as banks and telecommunication companies. Interviews and a structured questionnaire were the primary data of this study. The results of the study revealed that there is a positive significant relationship between Artificial Intelligence and Customer Experience. Artificial Intelligence explained 26.4% of the variance of the Customer Experience (R²= 0.264, F (1,89) =28.634, P< 0.05). Customer Experience has two dimensions; Customer Service and After-Sale Support, the study shows that Artificial Intelligence predicted 22.9% of the variance of Customer Service, whereas it predicted 7% of After-Sale Support. Moreover, providing Personalized Customer Service throughout the customer's buying journey has a great impact on Customer Experience. The study recommends enterprises to offer more personalized services for customers which it influences their overall experience with the enterprise. Likewise, it's highly recommended to employ Artificial Intelligence in call centers and the other after-sales support services to shortening the customers waiting time. Keywords: Customer Experience, Artificial Intelligence, Personalized Customer Service. JEL Classifications: M30, M31, M10 DOI: https://doi.org/10.32479/irmm.8166